Port Washington Civil War Draft Riot: National Implications of a Local Disturbance - Falch, Susan T. (My University, 2017)
Perceived unfairness in the appointment of county draft officials and German-speaking immigrants' general objection to conscription led to the 1862 Civil War draft riot in Port Washington, Wisconsin. One hundred and thirty men were arrested leading to three draft riot legal cases. In a difficult situation, the Wisconsin Supreme Court decided constitutional and legal questions illustrating how difficult it is to balance individual rights and state security during times of war.
Keywords: Draft Riot, Port Washington, Wis., 1862 Riots -- Wisconsin -- Port Washington Habeas corpus -- Wisconsin -- History -- 19th century Habeas corpus -- United States -- History -- 19th century; Draft Riot, Port Washington, Wis., 1862 Riots -- Wisconsin -- Port Washington Habeas corpus -- Wisconsin -- History -- 19th century; Draft Riot, Port Washington, Wis., 1862 Riots -- Wisconsin -- Port Washington; Draft Riot, Port Washington, Wis., 1862